Sharing the rides but are we sharing the profits? - Gambiza, T.; Pinto, Dale (Taxation Institue of Australia, 2016)
Ride-sharing services like Uber are posing major challenges to traditional taxation models. This is because business profits generated by Uber and similar companies are perceived to be “geographically divorced” from the provision of ride-sharing services themselves. To that extent, host countries that physically support the income-generating activities might lose out on the tax revenue because the “digital company” could be based in another country. This article considers the OECD’s BEPS project against companies like Uber to determine how and where profits are made, and how the concepts of source and residence are applied to characterise income for tax purposes in a consistent way. This article also seeks to establish: (1) the taxation models in Australia, France and the United States that are applied to capture taxable income; (2) how income tax is captured at a personal level earned from employment; and (3) the enforceability of regulations in different local governments.